The Potential of Antibodies Against the Phosphatidylserine / Prothrombin Complex as a Biomarker in Antiphospholipid Syndrome - Piotr Pasek; Witold Czyż; Julia Kulbacka; Julia Kacperczyk; Marta Chuncia-Ileczko; Michalina Wójcikiewicz; Filip Arczewski; Karol Dziedzic; Maciej Wojszczyk; Damian Zys; Julia Ryniecka (Journal of Education, Health and Sport)
Introduction